Bahasa, Budaya dan Realitas Budaya dalam Sastra - Sainil Amral; Sumiharti Sumiharti (Universitas Batanghari Jambi, 2022)
This study aims to review the relationship between language and culture and its implementation in literary works from a scientific point of view. Culturaldiversity enriches the language characteristics so that it is in betweenus to review a little of the relationship between language and culture and its implementation in literary works from a scientific point of view. This relates to bahasa being a tool used by humans to express ideas, ideas, and feelings by viewing culture as its semantic code. If we want to know the culture of a society then we can see and study from the language. The results of the discussion show that bahasa is a reflection of culture because inthe expression of the statement conveyed by someone we can trace the culture of that person. Â